LOS CUENTOS DEL CABALLERO DE BOUFFLERS EN EL SIGLO XIX - Antonio José De Vicente-Yagüe Jara (Anales de Filología Francesa)
In 1807, thirty seven years after publishing his licentious tale, Aline, reine de Golconde, which made him famous and represents his chef d’oeuvre, Boufflers published another two tales, La Mode and L’Heureux Accident, in the magazine Mercure de France as serials. Then, another collection consisting of an oriental tale entitled Le Derviche, and two short stories, Tamara ou Le Lac des pénitents, nouvelle indienne and Ah! si…, nouvelle allemande, was published in 1810. These moral tales, which were written during the first decade of the 19th century, show Boufflers’ conservative principles in his last years. They illustrate his intimate wish to retire from a disappointing society and to take shelter in the bosom of the family as a place where the individual may enjoy shared happiness, love and friendship in peace.